2021
DOI: 10.3390/ijms222111808
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected Interacting Effects of Physical (Radiation) and Chemical (Bisphenol A) Treatments on Male Reproductive Functions in Mice

Abstract: For decades, numerous chemical pollutants have been described to interfere with endogenous hormone metabolism/signaling altering reproductive functions. Among these endocrine disrupting substances, Bisphenol A (BPA), a widely used compound, is known to negatively impact germ and somatic cells in the testis. Physical agents, such as ionizing radiation, were also described to perturb spermatogenesis. Despite the fact that we are constantly exposed to numerous environmental chemical and physical compounds, very f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 71 publications
0
2
0
Order By: Relevance
“…Comparison of these DEGs with those identified after exposure to other EDCs indicated that 1 to 17 DEGs detected in F1 testes were also deregulated after exposure to the xenoestrogens bisphenol A (BPA) [ 86 ] and EE2 [ 87 ] and to the anti-androgenic EDCs di-2-ethylhexyl phthalate (DEHP) [ 88 ], DDT, and vinclozolin [ 89 ] ( Supplementary Table S9 ). Some genes that were also differentially expressed in F2 testes might be biomarkers of exposure to estrogenic ( Actn3 , Cntnap5b, Kcnk2 , Sall1 ) or anti-androgenic ( Dhrs4 , Fabp3 ) compounds.…”
Section: Resultsmentioning
confidence: 99%
“…Comparison of these DEGs with those identified after exposure to other EDCs indicated that 1 to 17 DEGs detected in F1 testes were also deregulated after exposure to the xenoestrogens bisphenol A (BPA) [ 86 ] and EE2 [ 87 ] and to the anti-androgenic EDCs di-2-ethylhexyl phthalate (DEHP) [ 88 ], DDT, and vinclozolin [ 89 ] ( Supplementary Table S9 ). Some genes that were also differentially expressed in F2 testes might be biomarkers of exposure to estrogenic ( Actn3 , Cntnap5b, Kcnk2 , Sall1 ) or anti-androgenic ( Dhrs4 , Fabp3 ) compounds.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, serum testosterone levels were also found to be significantly lower in BPA-treated mice at a dose of 20 mg/kg after 7 days of exposure [ 77 ]. StAR gene expression was found to be downregulated in embryo testes when pregnant mice were given drinking water contaminated with 10 µM of BPA in combination with radiation exposure [ 78 ]. The StAR protein was significantly reduced after 24 h of exposure to 70 mM of BPAF in the mouse Leydig cell tumor cell line (mLTC-1).…”
Section: Effect Of Bpa and Its Analogues On Star Protein Expressionmentioning
confidence: 99%